2016
DOI: 10.1016/j.msea.2016.01.057
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, phase composition and hardness evolution in 316L stainless steel processed by high-pressure torsion

Abstract: A 316L stainless steel was processed by high-pressure torsion (HPT) to evaluate the grain refinement and phase transformation. The initial material was essentially a single phase γ-austenite with a coarse-grained microstructure of ~42 µm but the grain size was reduced to ~45 nm after 10 turns of HPT. In addition, there was a phase transformation and the initial γ-austenite transformed initially to ε-martensite and finally to α'-martensite with increasing strain. The dislocation density increased to an exceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 35 publications
4
60
0
1
Order By: Relevance
“…The HPT deformation was carried out for low (N = ¼) and high (N = 10) numbers of revolutions. In an earlier study, the microtructures, the phase compositions and the hardness of these HPT-processed UFG 316L samples were studied in detail [5].…”
Section: Experimental Materials and Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…The HPT deformation was carried out for low (N = ¼) and high (N = 10) numbers of revolutions. In an earlier study, the microtructures, the phase compositions and the hardness of these HPT-processed UFG 316L samples were studied in detail [5].…”
Section: Experimental Materials and Proceduresmentioning
confidence: 99%
“…In addition to grain refinement, a simultaneous phase transformation also occurs during HPT with the transformation sequence γ-austenite → ɛ -martensite → α'-martensite. It was also revealed that the nanocrystalline grains yielded an exceptionally high hardness of ~6000 MPa after 10 turns of HPT [5]. It should be noted that the ultrahigh-strength martensitic steels often suffer from severe intergranular embrittlement which may lead to shorter operational lifetimes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations